International financial reporting standards as the basis of financial reporting for listed companies - Stanković, Predrag; Dimitrijević, Dragomir (Anali Ekonomskog fakulteta u Subotici, 2025)
The research explores the specificities and differences in the application of International Financial Reporting Standards (IFRS) as the basis for financial reporting by listed companies worldwide. The primary issue addressed is the inconsistency in IFRS application across countries, despite its global significance for the transparency and comparability of financial statements. The aim of the study is to identify the reasons behind the differences in the level of IFRS implementation across various jurisdictions, with a focus on listed companies, and to provide insights into the future directions of IFRS implementation. Methodologically, the research relies on the analysis of 168 jurisdictions whose profiles are available on the IFRS Foundation’s website. Data on the extent of IFRS application in domestic and foreign listed companies were analysed, including whether the adoption of the standards is mandatory or optional. The results indicate the dominance of jurisdictions where IFRS application is mandatory for listed companies, while specificities in the permissibility and scope of application are observed in other cases. These findings are relevant for analysts, investors, and regulators in assessing the effects of global harmonisation of financial reporting.